Molecular Characteristics of Nosocomial and Native American Community-Associated Methicillin-Resistant Staphylococcus aureus Clones from Rural Wisconsin - Shukla, Sanjay K. (American Society for Microbiology, 2004)
In central and northern Wisconsin methicillin-resistant Staphylococcus aureus (MRSA) was first detected in 1989. Over the next 10-year period, 581 MRSA isolates were collected, 17.2% of which came from patients who were treated at five Native American clinics. These isolates were typed by SmaI-macrorestricted pulsed-field gel electrophoresis (PFGE). The PFGE patterns clustered the isolates into six major clonal groups (MCGs), i.e., MCGs 1 to 6, and 19 minor clonal groups (mCGs). The 25 clonal groups were represented by 109 unique PFGE types. Sixty-five percent of the MCG-2 isolates were recovered from patients who were treated at Native American clinics. Ninety-four percent of the MCG-2 isolates harbored the staphylococcal cassette chromosome mec (SCCmec) IVa. These isolates also had PFGE profiles that were clonally related to the midwestern community-associated MRSA (CA-MRSA) strain, MW2. The representative isolates from MCG-2 had the multilocus sequence type allelic profile 1-1-1-1-1-1-1 and contained pvl genes. They were also susceptible to various antibiotics, a finding consistent with the CA-MRSA phenotype. SCCmec IV was also present in other mCGs. Unlike MCG-2, isolates from the remaining five MCGs harbored SCCmec II and were resistant to multiple antibiotics, suggesting their nosocomial origin. The 19 mCGs were represented by diverse SCCmec types and three putative new variants referred to as SCCmec Ib, IIa, and IIb.